2017
DOI: 10.1371/journal.pone.0183108
|View full text |Cite
|
Sign up to set email alerts
|

Can heat waves change the trophic role of the world’s most invasive crayfish? Diet shifts in Procambarus clarkii

Abstract: In the Mediterranean basin, the globally increasing temperatures are expected to be accompanied by longer heat waves. Commonly assumed to benefit cold-limited invasive alien species, these climatic changes may also change their feeding preferences, especially in the case of omnivorous ectotherms. We investigated heat wave effects on diet choice, growth and energy reserves in the invasive red swamp crayfish, Procambarus clarkii. In laboratory experiments, we fed juvenile and adult crayfish on animal, plant or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 70 publications
0
11
0
1
Order By: Relevance
“…Likewise, grasshoppers that could perceive the presence of a predator (spider) selected an intake target higher in carbohydrates than did controls (Hawlena & Schmitz, ). Other studies have shown that omnivorous invertebrates increase the relative intake of plant over animal tissue at higher temperatures (Boersma et al., ; Carreira, Segurado, Laurila, & Rebelo, ; Carreira et al., ; Malzahn, Doerfler, & Boersma, ), presumably to obtain extra carbon to meet the increased metabolic costs for ectotherms at higher temperatures (Boersma et al., ). Studies using chemically defined diets specifically showed that mealworms ( Tenebrio molitor L.) (Rho & Lee, ) and Spodoptera litura caterpillars (Lee, Jang, Ravzanaadii, & Rho, ) increased their preference for carbohydrate relative to protein at higher temperatures.…”
Section: Introductionmentioning
confidence: 97%
“…Likewise, grasshoppers that could perceive the presence of a predator (spider) selected an intake target higher in carbohydrates than did controls (Hawlena & Schmitz, ). Other studies have shown that omnivorous invertebrates increase the relative intake of plant over animal tissue at higher temperatures (Boersma et al., ; Carreira, Segurado, Laurila, & Rebelo, ; Carreira et al., ; Malzahn, Doerfler, & Boersma, ), presumably to obtain extra carbon to meet the increased metabolic costs for ectotherms at higher temperatures (Boersma et al., ). Studies using chemically defined diets specifically showed that mealworms ( Tenebrio molitor L.) (Rho & Lee, ) and Spodoptera litura caterpillars (Lee, Jang, Ravzanaadii, & Rho, ) increased their preference for carbohydrate relative to protein at higher temperatures.…”
Section: Introductionmentioning
confidence: 97%
“…The production exceeded 1 million tons with 37 billion USD output in 2017, accounting for 80% of global production according to FAO statistics (FAOSTAT, http://www.fao.org/faost at/en/) and Crayfish Industry Report 2018 (http://www.moa.gov.cn/). This is in contrast to the reality that it considered as an invasive species in Europe and Asia (Carreira et al 2017). The vigorous development of the industry was substantially attributed to the improved optimization of efforts involved in crayfish-rice farming, which original model has been practiced in Louisiana, USA for several decades (Si et al 2017a;Anastacio et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The Red Swamp Crayfish, Procambarus clarkii (Girard, 1852), native to south-central United States (Louisiana) and north-eastern Mexico, has been successfully introduced worldwide for commercial purposes. P. clarkii occupies a key position in invaded ecosystems, with dramatic impacts on ecosystem structure and functions (Gutiérrez-Yurrita et al, 1998; Alcorlo et al, 2004). This species is an omnivore with plants as the first food source (88.45% of occurrence in the stomachs of the crayfish studied) followed by animals (59.16%) and detritus (31.19%) (Gutiérrez-Yurrita et al, 1998).…”
Section: Introductionmentioning
confidence: 99%